Helping a New Breed of Private Water Operators Access Infrastructure Finance : Microfinance for Community Water Schemes in Kenya - Mehta, Meera (World Bank, Washington, DC, 2012)
Small-scale providers of water services are no longer seen as merely temporary substitutes for formal utilities. In many developing countries governments and donors increasingly view them as long-term partners in the work to extend and improve water services, particularly as governments accelerate efforts to meet water targets associated with the Millennium Development Goals. But a host of problems complicate efforts to make small-scale providers productive partners, including their lack of access to finance. In Kenya, a collaborative program is bringing together community-based organizations and micro-lenders to provide better water services to poor people -- and generating lessons for similar initiatives.